FORMATION OF EMOTIONAL INTELLIGENCE OF STUDENTS – FUTURE MUSIC TEACHERS AND MUSIC SUPERVISORS OF PRESCHOOL INSTITUTIONS - Kovalchuk, Vasyl; Ageykina-Starchenko, Tetiana; Chorna, Natalia; Iskra, Svitlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The reform of Ukrainian education has put forward new requirements for the training of teachers, in particular, future music teachers and music supervisors of preschool institutions. There was a need to revise traditional teaching methods, update the content of education and change emphasis in the educational process from cognitive to emotional. One of the factors affecting the professional training of a music teacher is emotional intelligence as integrated phenomenon that combines emotional and intellectual abilities into a single developing (dynamic) system, which gives the opportunity to distinguish cognitive-emotional, empathy-creative (artistic) and regulatory-behavioral components. The purpose of the article is the theoretical argumentation of the emotional intelligence concept and structure, the approbation results presentation of emotional intelligence formation methods by future music teachers and music supervisors of preschool institutions in the process of studying special music disciplines "Basic Special Instrument", "Voice Staging", "Choral Conducting". During the experimental research, which was conducted by students of the Preschool Education And Musical Art Faculty, various methods of diagnosing emotional intelligence were used, special methods and methods of its formation were created ("Self-knowledge", "Emotional infection", "Physical actions" methods; "What am I?", "Show your emotion", "Diary of emotions" techniques). It is proved that the implementation of the proposed methodological aspects into the educational process influences positive changes of this quality development, which, in turn, will ensure the successful adaptation of the future music teacher in his professional activity.